Design, construction, and in vivo feasibility of a positioning device for irradiation of mice brains using a clinical linear accelerator and intensity modulated radiation therapy. (2nd December 2017) - Rancilio, Nicholas J.; Dahl, Shaun; Athanasiadi, Ilektra; Perez-Torres, Carlos J.
Abstract: Purpose: The goal of this study was to design a positioning device that would allow for selective irradiation of the mouse brain with a clinical linear accelerator. Methods: We designed and fabricated an immobilization fixture that incorporates three functions: head stabilizer (through ear bars and tooth bar), gaseous anesthesia delivery and scavenging, and tissue mimic/bolus. Cohorts of five mice were irradiated such that each mouse in the cohort received a unique dose between 1000 and 3000 cGy. DNA damage immunohistochemistry was used to validate an increase in biological effect as a function of radiation dose. Mice were then followed with hematoxylin and eosin (H&E) and anatomical magnetic resonance imaging (MRI). Results: There was evidence of DNA damage throughout the brain proportional to radiation dose. Radiation-induced damage at the prescribed doses, as depicted by H&E, appeared to be constrained to the white matter consistent with radiological observation in human patients. The severity of the damage correlated with the radiation dose as expected. Conclusions: We have designed and manufactured a device that allows us to selectively irradiate the mouse brain with a clinical linear accelerator. However, some off-target effects are possible with large prescription doses.